1998
DOI: 10.1021/ie980220+
|View full text |Cite
|
Sign up to set email alerts
|

Equation of State Modeling of Phase Equilibrium in the Low-Density Polyethylene Process:  The Sanchez−Lacombe, Statistical Associating Fluid Theory, and Polymer-Soave−Redlich−Kwong Equations of State

Abstract: Applicability of the equation of state models for modeling and simulation of phase equilibrium in polymer production processes is investigated. The flash separation of unreacted ethylene from polyethylene is used as a prototype for simulation. First, three equation of state models (statistical associating fluid theory, Sanchez−Lacombe, and an augmented Soave−Redlich−Kwong cubic equation of state) are comparatively used to correlate pure component volumetric, calorimetric, and phase equilibrium properties for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 22 publications
1
65
0
Order By: Relevance
“…However, in addition to what was discussed in the previous publication [ 3 ] (where the original methodology was applied to a number of binary (penetrant/semicrystalline polymer) systems), it has been shown by various authors [ 4,7,[26][27][28][29][30] that properly fi tted binary interaction parameters enable the SL EoS to estimate various thermodynamic properties of mixtures involving semicrystalline polymers with an acceptable error (i.e., usually the error between experimental values and fi tted SL EoS values is less than 10%). Therefore, in this work the binary interaction parameters of the SL EoS were tuned to account for the effect of polymer crystallinity on gas(es) sorption in the polymer, at different temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to what was discussed in the previous publication [ 3 ] (where the original methodology was applied to a number of binary (penetrant/semicrystalline polymer) systems), it has been shown by various authors [ 4,7,[26][27][28][29][30] that properly fi tted binary interaction parameters enable the SL EoS to estimate various thermodynamic properties of mixtures involving semicrystalline polymers with an acceptable error (i.e., usually the error between experimental values and fi tted SL EoS values is less than 10%). Therefore, in this work the binary interaction parameters of the SL EoS were tuned to account for the effect of polymer crystallinity on gas(es) sorption in the polymer, at different temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 1998, different studies concluded that, even if able to correctly describe several system with high accuracy, EOS were not yet reliable tools for process simulation (Kim et al, 1998;Orbey, Bokis, & Chen, 1998).…”
Section: Equation Of State Approachmentioning
confidence: 99%
“…[3], [77]) and one using industrial plant data [65], a large number of SL EOS evaluations have been reported in the literature regarding liquid-liquid equilibrium.…”
Section: Modeling Polymeric Systems Using the Sanchez And Lacombe Equmentioning
confidence: 99%
“…Recently [2] presented and discussed in depth both classical and novel thermodynamic models, which have been developed and can potentially be used for industrial applications. A review of the use of some equations of state (EOS) for LDPE process simulation can be found in Orbey et al [3] and Valderrama [4].…”
Section: Introductionmentioning
confidence: 99%